On the taxonomy and phylogeny of the rare Selangor Mud Snake (Raclitia indica) Gray (Serpentes, Homalopsidae) from Peninsular Malaysia - Quah, Evan S.h.; Wood, Perry L. Jr.; Grismer, L. Lee; Sah, Shahrul Anuar Mohd (Zootaxa, 2018)
The taxonomic position of the rare Selangor Mud Snake (Raclitia indica) Gray to other species of homalopsids has remained uncertain due to the scarcity of specimens in collections and the lack of genetic material for comparison. Here we report the first molecular phylogenetic examination of this species based on recently acquired material. The study recovered R. indica nested within the clade of advanced, fanged homalopsids and the sister species to Erpeton tentaculatus Lácèpede. We also present notes on variation observed in the new specimens as well as range extensions for the species.